The Rating Form of IBD Patient Concerns: Translation, Validation, and First Implementation of the Greek Version. (26th April 2017) - Argyriou, Konstantinos; Roma, Eleftheria; Kapsoritakis, Andreas; Tsakiridou, Eirini; Oikonomou, Konstantinos; Manolakis, Anastassios; Potamianos, Spyridon
Abstract : Background . The rating form of IBD patients' concerns (RFIPC) provides a unique assessment of the worries and concerns of inflammatory bowel disease (IBD) patients. Our aims were primarily to validate the Greek version of RFIPC and secondarily to describe the pattern of Greek patients'concerns. Methods . After translating RFIPC, the questionnaire was given to IBD patients at baseline and after 12 weeks. The questionnaire's measuring properties were evaluated based on the consensus-based standards for the selection of health status measurement instruments (COSMIN) recommendations. Premediated factorial structures were tested for goodness of fit with confirmatory factor analysis (CFA). Results . At baseline, 200 patients (94 with Crohn's disease) completed RFIPC. After 12 weeks, the first 100 patients recompleted the questionnaire. CFA results were consistent with a slightly modified than the original factorial structure. Cronbach's α and intraclass correlation coefficients were high. RFIPC scores negatively affected the quality of life. RFIPC was sensitive to detect important changes in patients' condition and was able to discriminate between remission and active disease. Disease activity, full time employment, celibacy, and low education were associated with higher scores. Conclusion . The Greek version of RFIPC is a reliable, valid, and responsive tool to assess Greek IBD patients' concerns.